Identification of sources of resistance in cowpea mini core accessions to Aphis craccivora Koch (Homoptera: Aphididae) and their biochemical characterization - Togola, A.; Boukar, O.; Servent, A.; Chamarthi, S.; Tamo, Manuele; Fatokun, C. (Springer, 2020)
Cowpea (Vigna unguiculata (L. Walp) is an important grain legume for human and livestock nutrition, especially in sub-Saharan Africa. Aphid, Aphis craccivora Koch (Homoptera: Aphididae), is one of the most widespread and destructive insect pests of cowpea and host-plant resistance is an effective approach to minimize the pest damage at seedling stage. This study was aimed at identifying resistant sources to A. craccivora within the cowpea mini core collection, a set of accessions from the largest world cowpea germplasm collection maintained at the International Institute of Tropical Agriculture (IITA). A total of 375 lines including 373 from IITA mini core collection, one resistant (TVu-801) and one susceptible (TVx-3236) checks were evaluated through artificial infestation in screening cages during the seedling stage. In cages, genotypes were planted in single rows containing four plants. They were arranged in an augmented design in which the two checks were sown in individual cages. Scoring for aphid population and damage levels were carried out on individual plants at 7, 14, and 21 days after planting. Advanced bioassays and biochemical analyses were conducted to investigate the mechanism of resistance to A. craccivora. Overall, three genotypes TVu-6464, TVu-1583, and TVu-15445 showed good levels of resistance comparable to the resistant check TVu-801. The HPLC analyses proved that both low sucrose levels in the plant, as well as high levels of kaempferol and quercetin, aglycones of phenolic compounds, were related with high resistance to aphids. The above genotypes with promising levels of resistance to A. craccivora will be used in cowpea breeding programs to develop improved resistant lines against this pest.